Youth leadership and communication issues in Malaysia - Masduki Mohammad Morni, Mohd Yusri Ibrahim, Mohd Hazlami Jusoh,; Kasawani Ibrahim, Mohammad Mahdi Abas,; Yusof, Mat Rahimi; Sinin, Azhar Mohd (Opción, 2019)
Youth is an important asset to a country. Youth are the human capital of leadership in leading the country's development. They are also a leadership model for future generations. Based on these goals, the youth should have leadership and communication values within themselves. Leadership and communication are important entities to them. However, in this study, the results showed that today's youth face various issues related to leadership and communication. Today's youth are less skilled in good leadership and communication. Hence, this skill is an essential element for youths, in particular, to lead in organizations, associations or societies.